2019
DOI: 10.1186/s12940-019-0494-2
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to polychlorinated biphenyls and organochlorine pesticides and risk of dementia, Alzheimer’s disease and cognitive decline in an older population: a prospective analysis from the Canadian Study of Health and Aging

Abstract: Background: Little attention has been paid to neurotoxicants on the risk of dementia. Exposure to known neurotoxicants such as polychlorinated biphenyls (PCBs) and organochlorine (OC) pesticides is suspected to have adverse cognitive effects in older populations. Objective: To assess whether plasma concentrations of PCBs and OC pesticides are associated with the risk of cognitive decline, Alzheimer's disease (AD) and of all-cause dementia in the Canadian older population. Methods: Analyses were based on data f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 40 publications
1
23
0
1
Order By: Relevance
“…On the other hand, data from the Canadian Study of Health and Aging [48] showed instead a reduced prevalence of AD (2023 participants, 399 with AD) with elevated plasma pesticide (polychlorinated biphenyls (PCB) and organochlorine (OC)) metabolite levels [49]. A more recent analysis of the cohort (513 subjects, 108 with AD) also affirmed that there is no association of PCB and OC pesticides with the risk of dementia and AD, although a posteriori analyses showed that DDE levels are related to a higher cognitive decline in time [50].…”
Section: Epidemiological Links Between Pesticide Exposure and Alzheimmentioning
confidence: 99%
“…On the other hand, data from the Canadian Study of Health and Aging [48] showed instead a reduced prevalence of AD (2023 participants, 399 with AD) with elevated plasma pesticide (polychlorinated biphenyls (PCB) and organochlorine (OC)) metabolite levels [49]. A more recent analysis of the cohort (513 subjects, 108 with AD) also affirmed that there is no association of PCB and OC pesticides with the risk of dementia and AD, although a posteriori analyses showed that DDE levels are related to a higher cognitive decline in time [50].…”
Section: Epidemiological Links Between Pesticide Exposure and Alzheimmentioning
confidence: 99%
“…It is crucial to have a stable number of "close to unexposed" study subjects in the reference category to estimate a relative risk that is less biased . This methodological issue can explain the findings of Canadian elderly population with relatively high concentrations of POPs, which were discussed above …”
Section: Major Challenges For the Hypothesismentioning
confidence: 99%
“…In this paper, we distinguished between occupational or acciden- Chronic exposure to low-dose POPs was recently linked to cognitive impairment or dementia in the general population, although the results were not completely consistent. 24,[27][28][29][30] In cross-sectional and case-control studies performed on the U.S. general population, serum concentrations of OCPs were found to be related to an increased risk of dementia or cognitive impairment. 24,27 Interestingly, these compounds modified the well-known associations of established risk factors for cognition such as the apolipoprotein E (APOE) genotype, age, and hypertension.…”
Section: Lipophilic Chemical Mixtures As Neurotoxinsmentioning
confidence: 99%
“…), los PCB, el plomo, etc., podrían estar afectando al desarrollo cognitivo de las personas mayores. Sin embargo, existe todavía mucha controversia al respecto 41 , 42 , 43 , 44 .…”
Section: Contaminantes Ambientales Y Salud Mentalunclassified